Depiction of carbohydrate-active enzyme diversity in Caldicellulosiruptor sp. F32 at the genome level reveals insights into distinct polysaccharide degradation features. Issue 11 (13th November 2015) - Meng, Dong-Dong; Ying, Yu; Zhang, Kun-Di; Lu, Ming; Li, Fu-Li
<x xml:space="preserve">Abstract</x> Diverse and distinctive encoding sequences of CAZyme in the genome of Caldicellulosiruptor sp. F32 enable the deconstruction of unpretreated lignocellulose.